Oligomerization of propene over ZSM-5 modified with Cr and W - Alejandra María Santa Arango; Carlos Mario Escobar Garcés; José Luís Agudelo Valderrama; Alexander Guzmán Monsalve; Luz Amparo Palacio Santos; Adriana Echavarría Isaza (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
In this paper, the composition of ZSM-5 was modified with Cr and W by impregnation, isomorphous substitution and ion exchange, and the resulting catalysts were evaluated in the oligomerization of propene.